The role of N-acetyl-cysteine in the lung remote injury after hepatic ischemia and reperfusion in rabbits - Castro,Angela Potter de (2012)
PURPOSE: To study the lesions in the lung of rabbits caused by ischemia/reperfusion hepatic (I/R) after the use of N-acetyl-cysteine (NAC). METHODS: Twenty-four rabbits distributed in two groups: control group GI (n = 12) 5% glucose solution and experiment group GII (n = 12) NAC. The animals were pre-anesthetized with 1% acepromazine maleate and anesthetized with ketamine 10% and 2% xylazine intramuscularly. The GI and GII were given glucose solution intravenously or NAC 15min before occlusion of the hepatic pedicle (30 min). After the period of reperfusion of 24h (n = 6) or 48h (n = 6), liver and lung samples were collected for histology and immunohistochemistry to assess the impairment of cell. RESULTS: The animals of GII and GII-24h-48h showed parenchyma liver close to normal, when using NAC. The GII and GII-24h-48h showed lower thickness of alveolar cells that GI and GI-24h-48h. The expression of caspase 3 in lung cells GII presented smaller value compared to the GI group. CONCLUSION: N-acetyl-cysteine administered 15min prior to the injury ischemia/reperfusion had a significant protective role by minimizing lung injury and apoptotic morphology in the period observed.